Analysis of Adolescent Developmental Task Mastery and Its Implications for Information Service Materials - Sari, Dewi Purnama (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
This study aims to describe the mastery of developmental tasks of MAN Curup students and their implications for the preparation of information service materials. The method used is quantitative with a population of 75 students from MAN Curup majoring in Social Sciences. The sampling technique used is saturated sampling. Data were collected by using a questionnaire using the Guttman scale and analyzed by descriptive analysis. The results showed that some of the tasks of adolescent development have been mastered and some have not been mastered by students. Some developmental tasks that have not been mastered are maturity in establishing relationships with peers, economic independence, choosing and planning careers and understanding and implementing value systems and ethics in behaviour. Some aspects of developmental tasks that have not been mastered by students must be prioritized to be used as a basic reference in program preparation and implementation of counselling guidance services including in compiling information service materials